Peningkatan Aktivitas Komunikasi Interpersonal Dalam Organisasi Melalui Perbaikan Efikasi Diri, Kepemimpinan Dan Kekohesifan Tim - Hidayat, Rais (Universitas Kristen Satya Wacana, 2017)
The purpose of this research is to explain ways to improve communication, especially interpersonal communication in an organization through self-efficacy, leadership and team cohesiveness. This research uses quantitative research approach. Data analysis using path analysis. Research conducted in 2015 at 3 Private Universities in Bogor. Prior to use, the research instrument was piloted against 30 respondents to gain validity and reliability. Prior to hypothesis testing, test requirement analysis is tested linearity and normality test. The research findings are that interpersonal communication in the organization is positively and significantly influenced by self-efficacy, leadership behavior, and team cohesiveness. This means that the higher the self-efficacy, leadership behavior and team cohesiveness, the higher the interpersonal communication activity in the organization.